1989
DOI: 10.1002/eji.1830190418
|View full text |Cite
|
Sign up to set email alerts
|

On the cellular source and function of interleukin 6 produced in the central nervous system in viral diseases

Abstract: Interleukin 6 (IL6) was found to be produced in the central nervous system (CNS) of ICR+/+ mice infected with lymphocytic choriomeningitis virus (LCMV) or with vesicular stomatitis virus (VSV). When infecting athymic ICR nu/nu mice which cannot develop T cell-mediated meningitis after LCMV infection, no significant synthesis of IL6 was detected in the CNS. IL6 was found, however, to be produced intrathecally in ICR nu/nu mice infected with VSV, which causes a T cell-independent acute encephalitis. This suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
287
2
8

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 658 publications
(304 citation statements)
references
References 27 publications
7
287
2
8
Order By: Relevance
“…In neuron, TNFa can modulate calcium channels (Soliven and Albert, 1992), decrease catecholamine secretion (Soliven and Albert, 1992), alter synaptic transmission (Tancredi et al, 1992) and protect CNS neurons against metabolic-excitotoxic insults and promote calcium homeostasis (Cheng et al, 1994). IL-6 can induce astrocyte to secrete nerve growth factor (Frei et al, 1989). The ®ndings from this study as well as the many functions of IL-1, TNFa and IL-6 sustain the essential role of astrocytes in the immunologic response in brain under ischemia.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In neuron, TNFa can modulate calcium channels (Soliven and Albert, 1992), decrease catecholamine secretion (Soliven and Albert, 1992), alter synaptic transmission (Tancredi et al, 1992) and protect CNS neurons against metabolic-excitotoxic insults and promote calcium homeostasis (Cheng et al, 1994). IL-6 can induce astrocyte to secrete nerve growth factor (Frei et al, 1989). The ®ndings from this study as well as the many functions of IL-1, TNFa and IL-6 sustain the essential role of astrocytes in the immunologic response in brain under ischemia.…”
Section: Discussionmentioning
confidence: 64%
“…Relton and Rothwell (1992) have shown that the IL-1 receptor antagonist can reduce neuronal death induced by ischemia or excitotoxin. IL-1a is believed to be one of the key factors in triggering brain immune responses by inducing the expressions of IL-6 , Frei et al, 1989 and TNFa (Bethea et al, 1992;Chung and Benveniste, 1990). In neuron, TNFa can modulate calcium channels (Soliven and Albert, 1992), decrease catecholamine secretion (Soliven and Albert, 1992), alter synaptic transmission (Tancredi et al, 1992) and protect CNS neurons against metabolic-excitotoxic insults and promote calcium homeostasis (Cheng et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…10,12 Lopez-Cortes and colleagues 11 found that CSF levels of tumor necrosis factor-␣, IL-1␤, IL-6, and IL-8 were significantly higher in neurosurgical patients with bacterial meningitis than in patients with asymptomatic aseptic meningitis. These inflammatory cytokines are synthesized intrathecally by activated leukocytes 7,24 and were found to be more specific predictors of bacterial meningitis, compared with cell counts, in the study by Lopez-Cortes and colleagues. We analyzed the predictive and diagnostic value of IL-6 in neurosurgical patients with external drains.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, IL-6 may be a marker for injury severity and/or secondary insults under these experimental conditions, but due to the nonsignificant elevations, these results warrant further investigation. IL-6 may be produced by several different cell types after TBI or other types of acute injury (Frei et al, 1989;Woodroofe et al, 1991;Taupin et al, 1993;Clark et al, 1996;Hans et al, 1999;Reyes et al, 1999;Morganti-Kossmann et al, 2007;Suzuki et al, 2009;Lu et al, 2009;Yan et al, 2012). The evidence for local synthesis of IL-6 and other cytokines by resident cells, including neurons, glia, and endothelial cells, has been reported (Ott et al, 1994;Shohami et al, 1994;MorgantiKossmann et al, 1997;Feuerstein et al, 1998;Ghirnikar et al, 1998;Wang et al, 2001).…”
mentioning
confidence: 99%